SISTEM INFORMASI E-ARSIP BERBASIS WEB DI DANA PENSIUN JASA MARGA - Silva Ria Dinasty (2022)
Basically in an agency, information systems are needed to get more accurate information. Companies that still apply the Information System process manually will find it difficult to find data, for example in the Jasa Marga Pension Fund. Mail archive storage that is still done manually will be time consuming and inefficient, especially in searching for letters. Based on the above problems, a web-based E-Archive Information System was created at the Jasa Marga Pension Fund. This information system includes incoming mail, outgoing mail, adding and editing incoming mail and storage so that later it will facilitate the process of searching for incoming and outgoing mail. In this study, the method used is the waterfall method, the PHP programming language and MYSQL for database purposes in the process. The results are expected to be able to help Jasa Marga Pension Fund employees in storing archives of letters that are efficient in their use.